The Power of Stakeholders in the Management Compliance with Environmental Responsibility Issues in Indonesia - Juniarti Juniarti; Cynthia Karina; Lisa Lisa; Amelia Cicilia Tjahjono (Binus Business Review, 2019)
The objectives of this research were to find which the dominant stakeholders that pushed management to comply with the environmental responsibility and to examine the effect of environmental performance on financial performance. This research adopted Ullman’s three-dimensional framework to explain the stakeholders’ power. Stakeholders’ power was proxied by the power of shareholders, government, and customers. Then, PROPER rating measured the environmental performance. All Indonesian listed companies in all industrial sectors incorporating in the PROPER program were selected as the research sample. It resulted in 462 observations in the period of 2002-2017. PROPER was a company performance assessment program in environmental management. The Indonesian government initiated it through the Ministry of Environment and Forestry. This research also included various control variables (firm size, firm age, level of competitiveness, and leverage). Ordinary Least Square (OLS) was used to analyze data. The results show that the government’s power and customer’s power consistently influences the managers to comply with environmental issues. Meanwhile, the powers of the shareholder do not influence it. In the case of financial performance, the result supports the prior researchers that the higher rates of environmental performance are, the higher the powers of shareholders and customers will significantly be improved.